Prácticas de desmane en el desarrollo de dedos en el racimo de banano (Musa spp.) clon valery. - Ramírez Navarro, Hector Adolfo (2015)
The research was conducted at Hacienda Envy owned Noboa Group located in the canton Quevedo, Los Rios Province, between the geographical coordinates of 0° 52' 24" south latitude and 79° 23' 80" west longitude at an height of 73 meters, and lasted 120 days. The objective was to evaluate the development of fingers cluster of banana (Musa spp.) Clone Valery and its effect on production, for which a design is applied completely randomized (DCA) with 4 treatments and 4 replications, 10 floors used by repetition. All variables were subjected to analysis of variance. To measure differences between treatments means the Tukey test at 5% probability was used. From the results obtained treatment T1 (False 2 + 2 side / hand) has as many fingers scar insect damage with an average of 1.70; also shows the best results for the variable ratio, long fingers and exportable fruit boxes 1.56, 25.63 cm and 30.54 kg, likewise; He is the one with the best benefit with a profit of $ 5.17 and the best performance with a margin of 1.17; Treatment T2 (False 2 without side) is better in variables bunch weight (kg) and number of hands with 34.70 and 9.30 kg hands; also has the highest average 1.86 tip damage and the T1 (False 2 + 2 side / hand) treatment have the highest percentage of losses of fruit that does not qualify for export 10%. The treatment T4 (False 4 without side) had the highest degree of fingers with an average of 45.90 degrees, just as had the lowest percentage of shrinkage 5%.